Handbook of Thromboprophylaxis - Perry, David; Warwick, David (Springer International Publishing : Imprint: Adis, 2016)
This third edition expands upon the role of anticoagulants in clinical practice. In addition, it summarizes new developments in the field and provides evidence-based guidelines for the use of anticoagulants in routine day-to-day practice. The Handbook of Thromboprophylaxis Third Edition is a key resource for all physicians with an interest in thromboprophylaxis.